Pelatihan untuk masyarakat Indonesia di Jerman “women leadership” - Wazni Azwar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Community service as one of the tasks in the Tri Dharma of Indonesian Higher Education has tried to help the Indonesian people in Frankfurt Germany to facilitate community empowerment efforts, especially women with the theme